Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/jacs.1c12652
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Helical Assemblies of Dirhodium(II) Paddlewheels with 1,4-Diazabicyclo[2.2.2]octane: A Remarkable Substituent Effect on the Helical Sense Preference and Amplification of the Helical Handedness Excess of Metallo-Supramolecular Helical Polymers

Abstract: We report unique coordination-driven supramolecular helical assemblies of a series of dirhodium(II) tetracarboxylate paddlewheels bearing chiral phenyl-or methyl-substituted amidebound m-terphenyl residues with triethylene glycol monomethyl ether (TEG) or n-dodecyl tails through a 1:1 complexation with 1,4-diazabicyclo[2.2.2]octane (DABCO). The chiral dirhodium complexes with DABCO in CHCl 3 /n-hexane (1:1) form onehanded helical coordination polymers with a controlled propeller chirality at the m-terphenyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 139 publications
0
16
0
Order By: Relevance
“…[35,36] Meijer and co-workers notably found that lowering the temperature increases the extent of the S&S effect of BTA coassemblies by increasing the mismatch penalty value. [34] In addition to the temperature, [34,[37][38][39] parameters investigated to tune the S&S effect include the chemical nature of the "sergeants" [34,[37][38][39][40][41][42][43] or the "soldiers", [41] the concentration, [34] the solvent, [44,45] a physical field, [46] and additives. [47,48] The extent of the S&S effect is correlated to the number of defects, as quantified by the energetic values associated with helix reversals and chiral mismatches.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] Meijer and co-workers notably found that lowering the temperature increases the extent of the S&S effect of BTA coassemblies by increasing the mismatch penalty value. [34] In addition to the temperature, [34,[37][38][39] parameters investigated to tune the S&S effect include the chemical nature of the "sergeants" [34,[37][38][39][40][41][42][43] or the "soldiers", [41] the concentration, [34] the solvent, [44,45] a physical field, [46] and additives. [47,48] The extent of the S&S effect is correlated to the number of defects, as quantified by the energetic values associated with helix reversals and chiral mismatches.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular assembly is a powerful strategy for generating new collective properties (e.g., helicity and porosity) beyond the characteristics of individual molecules. To construct a specific supramolecular entity, a predictable molecular assembly behavior based on the molecular structure is essential. However, the design of an extrinsic porous supramolecular framework remains to be a challenging task because the intermolecular interactions are much weaker than the coordination or covalent bonds in the well-established porous frameworks such as metal–organic frameworks and covalent organic frameworks .…”
Section: Introductionmentioning
confidence: 99%
“…To build structural mimics of such constructs, helical metal-ligand assemblies have been investigated extensively. [7][8][9][10][11][12][13][14][15][16][17] Studies on metallohelicates have focused primarily on topological design, 10,[18][19][20][21] stereoselective synthesis, [22][23][24][25][26] chiroptical application, [26][27][28][29] and DNA binding properties. [30][31][32][33][34] Within this context, only a handful of works explored the dynamic aspects of helical metal complexes.…”
Section: Introductionmentioning
confidence: 99%